Feasibility and Outcomes of Upgrading to Left Bundle Branch Pacing in Patients With Pacing-Induced Cardiomyopathy and Infranodal Atrioventricular Block - Ye, Yang; Wu, Shengjie; Su, Lan; Sheng, Xia; Zhang, Jiefang; Wang, Bei; Sharma, Parikshit S.; Ellenbogen, Kenneth A.; Su, Yangang; Chen, Xueying; Fu, Guosheng; Huang, Weijian (Frontiers in Cardiovascular Medicine, 2021)
His bundle pacing (HBP) can reverse left ventricular (LV) remodeling in patients with right ventricular (RV) pacing-induced cardimyopathy (PICM) but may be unable to correct infranodal atrioventricular block (AVB). Left bundle branch pacing (LBBP) results in rapid LV activation and may be able to reliably pace beyond the site of AVB. Our study was conducted to assess the feasibility, safety, and outcomes of permanent LBBP in infranodal AVB and PICM patients. Patients with infranodal AVB and PICM who underwent LBBP for cardiac resynchronization therapy (CRT) were included. Clinical evaluation and echocardiographic and electrocardiographic assessments were recorded at baseline and follow-up. Permanent LBBP upgrade was successful in 19 of 20 patients with a median follow-up duration of 12 months. QRS duration (QRSd) increased from 139.3 ± 28.0 ms at baseline to 176.2 ± 21.4 ms (P < 0.001) with right ventricular pacing (RVP) and was shortened to 120.9 ± 15.2 ms after LBBP (P < 0.001). The mean LBBP threshold was 0.7 ± 0.3 V at 0.4 ms at implant and remained stable during follow-up. The left ventricular ejection fraction (LVEF) increased from 36.3% ± 6.5% to 51.9% ± 13.0% (P < 0.001) with left ventricular end-systolic volume (LVESV) reduced from 180.1 ± 43.5 to 136.8 ± 36.7 ml (P < 0.001) during last follow-up. LBBP paced beyond the site of block, which results in a low pacing threshold with a high success rate in infranodal AVB patients. LBBP improved LV function with stable parameters over the 12 months, making it a reasonable alternative to cardiac resynchronization pacing via a coronary sinus lead in infranodal AVB and PICM patients.